The critical periods of cerebral plasticity: A key aspect in a dialog between psychoanalysis and neuroscience centered on the psychopathology of schizophrenia - Tran The, Jessica; Magistretti, Pierre J.; Ansermet, Francois (Frontiers in Molecular Neuroscience, 2022)
Through research into the molecular and cellular mechanisms that occur during critical periods, recent experimental neurobiological data have brought to light the importance of early childhood. These have demonstrated that childhood and early environmental stimuli play a part not only in our subjective construction, but also in brain development; thus, confirming Freud’s intuition regarding the central role of childhood and early experiences of the environment in our psychological development and our subjective outcomes. ‘Critical periods’ of cerebral development represent temporal windows that mark favorable, but also circumscribed, moments in developmental cerebral plasticity. They also vary between different cortical areas. There are, therefore, strictly defined temporal periods for learning language, music, etc., after which this learning becomes more difficult, or even impossible, to acquire. Now, research into these critical periods can be seen as having a significant part to play in the interdisciplinary dialogue between psychoanalysis and neurosciences with regard to the role of early experiences in the etiology of some psychopathological conditions. Research into the cellular and molecular mechanisms controlling the onset and end of these critical periods, notably controlled by the maturation of parvalbumin-expressing basket cells, have brought to light the presence of anomalies in the maturation of these neurons in patients with schizophrenia. Starting from these findings we propose revisiting the psychoanalytic theories on the etiology of psychosis from an interdisciplinary perspective. Our study works from the observation, common to both psychoanalysis and neurosciences, that experience leaves a trace; be it a ‘psychic’ or a ‘synaptic’ trace. Thus, we develop a hypothesis for an ‘absence of trace’ in psychosis; reexamining psychosis through the prism of the biological theory of critical periods in plasticity.